Habitat associations and behavioural patterns of Symphodus spp. (Pisces: Labridae) - Rodrigues, Diana (2020)
The complexity and diversity of physical and biotic habitats are important features influencing the composition of shallow water reef fish assemblages, especially in temperate regions where abundant and diverse algal cover may have an important habitat-forming role. Coastal fish have adapted to these diverse habitats and to the temporal and spatial variations of algal assemblages in different ways. Wrasses are an important group of coastal rocky reef fish which present particular associations to algae in temperate systems. In this study, habitat associations were analysed in three species of wrasses: Symphodus bailloni, Symphodus melops and Symphodus roissali, and their behaviour was recorded. Eight main behavioural categories (comprising a total of 42 different behaviours) were identified: exploring, foraging, resting, agonistic interactions, cleaning, courtship, reproduction and nesting. S. melops occurred on shallower depths and was frequently involved in both intra- and interspecific agonistic interactions with the other wrasse species, although rarely with S. bailloni. S. roissali was associated with microhabitats of smaller size where it frequently hides. Feeding occurred mostly on bedrock habitat when compared to other microhabitats. Foraging and resting showed a marked seasonality in the three wrasses, related to shifts in biotic habitat structure and to changes in the behavioural repertoire during the breeding season.